Dynamic Analysis for Bertrand Competition Model with Exponential Form*. Issue 6 (1st November 2016) - Ma, Huili; Feng, Hui
Abstract: This paper will consider a nonliear system of difference equations which describes a qualitative study of Bertrand oligopoly games with two boundedly rational players. With nonlinear demand function of exponential form, the local stability of equilibria and the global convergence of positive solutions for the dynamical system are analyzed.